2021
DOI: 10.1177/20533691211058030
|View full text |Cite
|
Sign up to set email alerts
|

British Menopause Society tools for clinicians: Progestogens and endometrial protection

Abstract: Progestogen administration is required to oppose naturally produced or administered estrogens to provide endometrial protection. Within HRT regimens, this should be delivered for at least the same duration as that produced during the luteal phase of the monthly cycle and in the recommended doses to protect against the risk of endometrial hyperplasia and endometrial cancer. This includes progestogens administered for 12–14 days a month in sequential regimens and continuous daily intake in continuous combined HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The authors concluded that both 0.25 and 0.5 mg norethrindrone provides adequate protection. A British Menopause Society publication using the same data came to a more conservative recommendation of 0.5 mg norethrindrone 54. In the US, only a 0.35 mg pill is available.…”
Section: Menopausal Hormone Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that both 0.25 and 0.5 mg norethrindrone provides adequate protection. A British Menopause Society publication using the same data came to a more conservative recommendation of 0.5 mg norethrindrone 54. In the US, only a 0.35 mg pill is available.…”
Section: Menopausal Hormone Therapymentioning
confidence: 99%
“…One small RCT that randomized women to estradiol 0.05 mg patch with continuous oral micronized progesterone 100 mg or 200 mg or vaginal progesterone 100 mg or 200 mg daily showed no significant differences in endometrial thickness at 12 month follow-up but provided no histologic outcomes. If using micronized progesterone capsules vaginally, equivalent dosing to oral dosing is suggested, even though vaginal absorption and effective dose to the uterus may be higher with this route of administration 54…”
Section: Menopausal Hormone Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Current guidance recommends NET 5 mg is taken for 12 days in sequential HRT regimes and NET 0.5–1 mg is taken daily in continuous HRT regimes. 39 It is estimated that 1 mg of orally administered NET metabolises to 4–6 µg ethinylestradiol. 40 Considering the thromboembolic risk associated with ethinylestradiol, this conversion may be clinically significant in women at increased risk for VTE.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be considered after 12-18 months of sequential use, if women want to try ccHRT to see if they can achieve a bleed-free regimen at an earlier point. 25 Tricycling (Long-cycle) progestogen use and shortened progestogen regimens. This is where estrogen is given daily but a reduced progestogen course (7-10 days) is given every 3 months.…”
Section: Major Risk Factorsmentioning
confidence: 99%